Navigating uncertainty: trouble in Haven. (June 2017) - Sexton, Max
Abstract : The adaptation to television of the novels of Stephen King differs from that to film and raises questions about medium specificity, as well as the extent to which the adaptation of King's work may have become increasingly complex. Haven (2010–15) expands the horror genre and segues with sf. Such a development marks how the specific threat (vampire, etc.) against the primary protagonist has been modified with an undefined threat. Such notions are shown as a set of multiple meanings as key questions are raised about the town's supernatural 'Troubles' and the character of Audrey Parker's own relationship to them. Haven works by defining American (small-town) life as a collection of personal histories. In Audrey's quest for certainty about her identity, the ambiguous and the interplay between normality and the horrific indicates a broader linking of different worlds that creates a multiverse. In these ways, in Haven, generic content is destabilised within the adaptation of King's work to television and can be used to explore how hybridity can be understood and defined in relation to notions of specific media.